PUBLIC SERVICE MALLS AS A SOLUTIION IN IMPROVING THE QUALITY OF PUBLIC SERVICES IN INDONESIA - Putri Wulandari Atur Rejeki (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2022)
One of public service transformation carried out by the government is by building Public Service Malls (PSM). To date, more than 30 regencies/cities have had PSM. This study aims to analyze the extent to which the PSM built by the regencies/city government is significantly able to improve public services in the region. The study uses a quantitative method by comparing the quality of public services as measured by the value of the Public Service Index (PSI) in 2020 for groups of regencies/cities that already have PSM (30 regions) with groups that do not yet have PSM (191 regions). The normality test for the group of regencies/cities that do not yet have PSM shows the p-value of the Kolmogorov-Smirnov of 0.001. This means that the regional group is not from a normal population. The Mann-Whitney test was used to continue data analysis. The results of the Mann-Whitney Test were 2145,500 with a p-value of 0.027 (2-tailed, =0.05). The study found that the quality of public services provided by government regencies/cities that have a PSM is significantly better than those without a PSM. The most important factor in improving the quality of regencies/city government public services in Indonesia is the service policy.